Prevalence of Moraxella catarrhalis in patients of lower respiratory tract infection with underlying risk factors - Aiswariya, Alex; Suseela, Kundoly Velayudhan; Subi, Das (International Journal of Advances in Medicine, 2017)
Background: Moraxella catarrhalis is a Gram-negative diplococcus, commonly found as a normal flora in the human upper respiratory tract. Recently, M. catarrhalis has emerged as an important and common human respiratory tract pathogen. This study was aimed to determine the rate of isolation of M. Catarrhalis in patients attending a tertiary care hospital with lower respiratory tract infection (LRTI), antibiotic susceptibility pattern and predisposing factors responsible for their infection. Methods: A prospective study was carried out in 1001 lower respiratory specimens from patients (above 20 years’ age) with suspected LRTI. The study investigated by microscopic examination, culture and antibiotic sensitivity test according to the standard guidelines. Assessment of clinical significance of M. Catarrhalis was ascertained on the basis of preformed criteria. Results: A total of 60 clinically significant M. Catarrhalis were isolated from the 930 culture positive samples. The isolates showed maximum sensitivity to second and third generation cephalosporins (95%), azithromycin (90%) followed by amoxicillin clavulanic acid (85%). Rate of isolation was more in males (70%) and elderly people above 60 years (63.33%) were found to be more affected. Patients (58.33%) with Chronic Obstructive Pulmonary Diseases (COPD) were found to be more prone to get infection by M. Catarrhalis. Conclusions: Moraxella catarrhalis should be considered as significant lower respiratory tract pathogen especially in elderly patients with underlying risk factors like COPD.